ROLE OF NATIONAL POLICIES IN DEVELOPMENT OF CONSTITUTIONAL VALUES AMONG STUDENTS - Mishra, Rahul; Agarwal, Amit Kumar (ShodhKosh: Journal of Visual and Performing Arts, 2024)
In this article, constitutional values ​​have been described through the textbooks of school education and an attempt has been made to clarify that education is the carrier of constitutional values. To fulfill constitutional values, constitutional-value centered curriculum and lessons of textbooks are based. Creating a sense of coordination and brotherhood among citizens, protecting the dignity and freedom of the individual, as well as being aware of constitutional values ​​is possible only through education. Education teaches the nation and the individual to respect and honor the rights and needs of the deprived and the needy. In this way, constitutional values ​​are fulfilled by sitting in the boat of education. Fulfillment of constitutional values ​​binds a diverse nation together. The present article explains the role of various national education policies in developing constitutional values ​​in a student or future citizen. Also, it explains the development of constitutional values ​​through the lessons of school textbooks prepared on the basis of national education policies. The writers have tried to show various values ​​from the textbooks available in school education such as social justice and equality, faith and belief, national integrity, dignity of the individual etc. While highlighting various values ​​in the books, they have also tried to interpret the stories in the same context.